Negative regulation of the rat stromelysin gene promoter by retinoic acid is mediated by an AP1 binding site. - Nicholson, R C (1990)
Stromelysin is a member of the metalloproteinase family which plays an important role in extracellular matrix remodelling during many normal and disease processes. We show here that in polyomavirus-transformed rat embryo fibroblast cells (PyT21), the transcription from the stromelysin gene is repressed by the vitamin A derivative retinoic acid (RA). Furthermore, expression vectors encoding the human RA receptors hRAR-alpha, hRAR-beta and hRAR-gamma repress chloramphenicol acetyltransferase (CAT) expression from stromelysin promoter-CAT gene expression vectors in RA-treated PyT21 and human HeLa cells, as determined by transient transfection assays. Through mutation and deletion analysis, we show that the RA dependent repression is mediated by a 25 bp region from nucleotide positions -72 to -48 of the rat stromelysin 5'-flanking DNA sequence. Further mutation analysis of this region indicates that the DNA sequence required for RA dependent repression colocalizes with an AP1 binding site which is essential for promoter activity. We show also that RA represses the transcriptional activity of a reporter gene containing a TPA responding AP1 binding site driving the HSV tk promoter. Thus the RAR-RA complex appears to repress transcription of the stromelysin gene by blocking activation by positive regulatory factors. However, we found no evidence supporting the possibility that the RA dependent repression could be due to RAR binding to the AP1 binding site or to the AP1 components c-fos and c-jun.